The role of IFT20 mediated by neuropeptide FILa1 in ciliary activity during larval settlement of Urechis unicinctus - Zhang, Long; Zhang, Wenqing; Lai, Wenyuan; Yang, Zhi; Lin, Dawei; Zhang, Zhengrui; Zhang, Zhifeng (Frontiers in Marine Science, 2025)
BackgroundSettlement and metamorphosis are crucial developmental events in the life cycles of most marine benthic invertebrates. Neuropeptides play an important role in inducing larval settlement. However, studies on the ciliary genes and the few studies have examined the pathways regulated by neuropeptides during larval settlement.MethodsHere, we employed multiple molecular biology techniques to identify a ciliary gene, intraflagellar transport protein 20 (IFT20) which played a significant role in the larval settlement of Urechis unicinctus (Annelida, Echiura), and revealed the related gene pathway of IFT20 expression regulated by FILa1, a neuropeptide unique to U. unicinctus.ResultsThe IFT20 protein of U. unicinctus was highly conserved with that of other animals and localized at the ciliary base in the trochophore and the segmentation larvae of U. unicinctus. It was determined that the neuropeptide FILa1 inhibits IFT20 expression through the cAPM-PKA-CREB and Ca2+ pathways, which in turn triggers larval settlement. Knockdown the mRNA level of IFT20 resulted in a reduction in the number of vesicles at the ciliary base, the β-tubulin protein synthesis, the number and length of cilia, and the beat frequency of the circumoral cilia. Finally, the settlement rate of the larvae in the IFT20-dsRNA group increased by 3.64 times and 2.88 times compared to the control group at 48 and 72 h, respectively.ConclusionOur findings provide new insights into the function of IFT20 and the signaling pathways through which neuropeptides regulate ciliary gene expression during larval settlement.